SARRES FUN LEARNING MODEL BASED ON DEEP LEARNING FOR IMPROVING CHILDREN'S READING COMPREHENSION IN THE COMMUNITY READING CENTER - Sri Daning Aprianti; Sisca Rahmadonna (Universitas Labuhanbatu, 2026)
Purpose – This study aims to analyze the impact of implementing the SARRES Fun Learning model, grounded in the principles of Deep Learning (mindful, meaningful, and joyful learning), on improving children's reading comprehension skills at the Community Reading Center (TBM) using Barrett's Taxonomy.Methodology – The study used a quantitative approach with a one-group pretest-posttest pre-experimental design. The research subjects consisted of 36 elementary school children selected through purposive sampling. The intervention was conducted over four sessions by applying the six stages of SARRES (Survey, Ask, Read Aloud, Review, Engage, and Share). Data were collected using a validated and reliable reading comprehension test and analyzed using descriptive statistics, paired-samples t-tests, and normalized gain.Findings – The results showed a significant improvement in children's reading comprehension skills, with the average score increasing from 34.97 to 55.89 (t = −16.950; p < 0.05). The n-gain value of 0.55 indicates moderate learning effectiveness and an improvement in all Barrett Taxonomy indicators.Contribution – The novelty of this study lies in the empirical testing of the application of the SARRES Fun Learning model, implemented using Deep Learning principles in the context of non-formal literacy at the Community Reading Park (TBM). This research expands the empirical evidence on the effectiveness of adapting the SQ3R strategy in non-formal learning environments. It provides practical implications as an alternative, systematic, and applicable reading-learning strategy for TBM managers and facilitators.